1992
DOI: 10.1161/01.cir.85.6.2162
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of atrioventricular nodal reentrant tachycardia using discrete slow potentials to guide application of radiofrequency energy.

Abstract: An area showing slow potentials is present at the perinodal region in humans. In patients with AVNRT, application of radiofrequency energy renders tachycardia noninducible through the preferential modification of the anterograde slow pathway. With present clinical methods, the exact origin and significance of these physiological potentials cannot be specified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
268
2
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 545 publications
(292 citation statements)
references
References 47 publications
18
268
2
4
Order By: Relevance
“…These SPs showed a low amplitude with a slow rate of rise morphology and they were observed along the tricuspid annulus. McGuire et al20, 21 previously reported that high‐frequency deflection followed by a low‐frequency deflection, which is similar to that described by Haissaguerre et al,1 were found during sinus rhythm along the tricuspid annulus. These potentials were caused by asynchronous activation of 2 cell layers, a high‐frequency component was caused by depolarization of atrial‐type cells in the deep subendocardial layer and the low‐frequency component was caused by depolarization of cells with nodal characteristics close to the endocardium 20, 21.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…These SPs showed a low amplitude with a slow rate of rise morphology and they were observed along the tricuspid annulus. McGuire et al20, 21 previously reported that high‐frequency deflection followed by a low‐frequency deflection, which is similar to that described by Haissaguerre et al,1 were found during sinus rhythm along the tricuspid annulus. These potentials were caused by asynchronous activation of 2 cell layers, a high‐frequency component was caused by depolarization of atrial‐type cells in the deep subendocardial layer and the low‐frequency component was caused by depolarization of cells with nodal characteristics close to the endocardium 20, 21.…”
Section: Discussionsupporting
confidence: 76%
“…The SP was defined as a discrete and low amplitude deflection with a slow rate of rise occupying the interval between the atrial and ventricular potentials 1, 3. The electrogram amplitude and width of the atrial electrogram and the SP were measured during sinus rhythm and compared between the successful and unsuccessful ablation sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Mapping of the cardiac chambers is performed with relatively stiff manually deflectable catheters with unidirectional or bidirectional deflection radius. Steering of those electrodes is performed via a pull-wire mechanism integrated in the handle of the catheter, allowing a reliable and reproducible deflection.…”
mentioning
confidence: 99%
“…4 Indeed, several investigators provided evidence that slow, low-amplitude waves could be recorded between atrial and His bundle potentials. [5][6][7] In the process of developing radiofrequency catheter ablation for the termination and cure of AVN reentrant tachycardia, potentials recorded in the inferior-posterior portion of Koch's triangle, both in animals 8 and in man, 5,6 served as the targets for successful ablation of slow AVN input. However, it remains unclear if surface potentials from the AVN can carry the distinctive signatures of "slow" and "fast" wavefronts that form the foundation of dual AVN physiology.…”
mentioning
confidence: 99%